HIGHER EDUCATION AND SOCIETY: RUSSIA AND OTHER COUNTRIES - Anatoliy I. Rakitov; Alina E. Anisimova (Высшее образование в России)
Higher education is an institute of excellent importance for society and its development deeply depends on public support. It’s impossible to score a success with poor finance, bad infrastructure and without legal protection. As a result the quality of education steadily deteriorates. To rely on higher education as s solemn remedy to ensure future prosperity and wealth is a mistake. The other key factors are important for increasing social effect of education on wellAbeing, such as social family capital and parent’s income. The quality of education is closely connected with employer’s satisfaction with diploma holders qualification. The practice of employers polling is not so widespread in Russian regions as it is in other countries. The distant education is also of scrupulous attention. The main method in thearticle is the method of comparative analysis.